Effects of Planned FFI on Learners' Acquisition of Present Perfect - Deocampo, Lynnie Ann P. (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2013)
This study examined the effects of planned form focused instruction (FFI) on the acquisition of present perfect tense identified as one problematic structure for 60 young adult learners undergoing English remediation in a University College Bound Program. The study addressed these issues: 1. How are learners attention drawn to notice the target form while focusing on its meaning and use? 2. If taught using planned FFI, will there be significant and sustained gains in learners' accuracy across time? Research method involved measuring learners current grammar competence and accuracy gains through one immediate and two delayed post tests, and examining their learning behaviours during sessions and tests. The study yielded these significant findings: Enriched input, noticed target structure, and, consequently, acquisition of it were facilitated through flooding or enhancement, recast, reformulation and other pre-planned consciousness-raising techniques during communicative activities. Accuracy gains were evident and sustained across time. Learners generally enjoyed engaging in interactive activities and were challenged to answer rule inducing questions after completing classroom tasks.In conclusion, planned FFl effectively facilitated acquisition of the form in focus when delivered with a communicatively rich subject-matter and with strategic opportunities for output and feedback enabling learners to proceduralise their knowledege of grammar.